THE INFLUENCE OF BRAND LOYALTY, BRAND AWARENESS, AND PERCEIVED QUALITY ON CONSUMER BUYING DECISION OF YAMAHA VIXION MOTORCYCLE IN MANADO - Rantung, Wensy; Saerang, David P.E.; Mekel, Peggy Adeline (Universitas Sam Ratulangi, 2014)
In the modern society brand not only represent the product or company but also have a strong association with perceived quality, consumers’ life style, consumer loyalty. The purpose of this study is to create a deeper consideration of what the influence of brand loyalty, brand awareness, and perceived quality can have, when people go for purchasing, choose the products between different brands, especially private vehicle like motorcycle. This study also tries to explore the relation between brands loyalty, brand awareness, and perceived quality and the consumer decision making process to buying motorcycle in Manado. The research method associate with multiple linear regression analysis technique with 100 respondents as sample of the research taken from people in Manado as consumers of motorcycle. From the study it is revealed that when consumer choose to purchasing one of some brand motorcycle, it's because they are influenced of brand loyalty, brand awareness and perceived quality. And this study also reveals that branded motorcycle have a great place in consumer mind, when customers go for purchasing a motorcycle they prefer to purchase a well know branded motorcycle. Keywords: brand loyalty, brand awareness, perceived quality, buying decision